BTLA inhibition has a dominant role in the cis-complex of BTLA and HVEM - Battin, Claire; Leitner, Judith; Waidhofer-Söllner, Petra; Grabmeier-Pfistershammer, Katharina; Olive, Daniel; Steinberger, Peter (Frontiers in Immunology, 2022)
The engagement of the herpesvirus entry mediator (HVEM, TNFRSF14) by the B and T lymphocyte attenuator (BTLA) represents a unique interaction between an activating receptor of the TNFR-superfamily and an inhibitory receptor of the Ig-superfamily. BTLA and HVEM have both been implicated in the regulation of human T cell responses, but their role is complex and incompletely understood. Here, we have used T cell reporter systems to dissect the complex interplay of HVEM with BTLA and its additional ligands LIGHT and CD160. Co-expression with LIGHT or CD160, but not with BTLA, induced strong constitutive signalling via HVEM. In line with earlier reports, we observed that in cis interaction of BTLA and HVEM prevented HVEM co-stimulation by ligands on surrounding cells. Intriguingly, our data indicate that BTLA mediated inhibition is not impaired in this heterodimeric complex, suggesting a dominant role of BTLA co-inhibition. Stimulation of primary human T cells in presence of HVEM ligands indicated a weak costimulatory capacity of HVEM potentially owed to its in cis engagement by BTLA. Furthermore, experiments with T cell reporter cells and primary T cells demonstrate that HVEM antibodies can augment T cell responses by concomitantly acting as checkpoint inhibitors and co-stimulation agonists.